O poder instrutório do julgador na fase recursal do processo civil em busca da verdade provável - Dias, Luciano Souto (2017)
Based on truth premises, process and justice, as a search line, the present dissertative work includes a critical and reflexive pioneer analysis regarding judge’s instructive power in civil process recursal phase, in search of probable truth. The dissertative construction approaches the theme from procedural dynamics evolution in its dogmatic and pragmatic aspects, glimpsing the judge’s probative initiative indispensability as a preponderant factor so that the judicial performance is efficient and fair. From the syncretism to the valorative formalism, from inquisitorial and adversarial systems to the cooperative model in modern procedural systematics, the research highlights legal thought evolution in the contemporary scenario, notably by publicist vision prevalence and the directives stemming from process constitutionalisation. Based on procedural technological facilities, the mechanicism in proceedings treatment in the recursal phase is criticized, defending a greater proof valorization in the recursal phase from the necessary merit primacy, with tests realization prioritized in the own court, which finds significant normative support in the Code of Civil Procedure of 2015, which contemplates innovative procedural paradigms, making perceptible the adoption of practices based on cooperation and procedural dialectics valorization, in order to protect material legal relationship confrontation and jurisdictional guardianship effectiveness with peculiarities and complexities adequacy to each demand, through a fair and efficient process. From normative parameters and the dialogue with the doctrinal and jurisprudential positioning, and without aiming to exhaust the subject, the research aims to contribute to the foment of new debates and reflections on the subject under consideration. The work contemplates a defense of a new view on evidence in recursal phase from the new brazilian procedural regulation, seeing judge’s probative activity as a power and a technique capable of contributing to reach the probable truth of the facts that refer to the demand, which will make possible, in the process, the effective judicial action in search of rights realization, fundamental guarantees and material justice itself.